A meta-analysis for the echocardiographic assessment of right ventricular structure and function in ARVC: a Study by the Research and Audit Committee of the British Society of Echocardiography. Issue 3 (September 2016) - Qasem, Mohammad; Utomi, Victor; George, Keith; Somauroo, John; Zaidi, Abbas; Forsythe, Lynsey; Bhattacharrya, Sanjeev; Lloyd, Guy; Rana, Bushra; Ring, Liam; Robinson, Shaun; Senior, Roxy; et al.
Abstract : Introduction: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited pathology that can increase the risk of sudden death. Current task force criteria for echocardiographic diagnosis do not include new, regional assessment tools which may be relevant in a phenotypically diverse disease. We adopted a systematic review and meta-analysis approach to highlight echocardiographic indices that differentiated ARVC patients and healthy controls. Methods: Data was extracted and analysed from prospective trials that employed a case–control design meeting strict inclusion and exclusion as well as a priori quality criteria. Structural indices included proximal RV outflow tract (RVOT1 ) and RV diastolic area (RVDarea ). Functional indices included RV fractional area change (RVFAC), tricuspid annular systolic excursion (TAPSE), peak systolic and early diastolic myocardial velocities (S′ and E′, respectively) and myocardial strain. Results: Patients with ARVC had larger RVOT1 (mean ± s.d. ; 34 vs 28 mm, P < 0.001) and RVDarea (23 vs 18 cm 2, P < 0.001) compared with healthy controls. ARVC patients also had lower RVFAC (38 vs 46%, P < 0.001), TAPSE (17 vs 23 mm, P < 0.001), S′ (9 vs 12 cm/s, P < 0.001), E′ (9 vs 13 cm/s, P < 0.001) and myocardial strain (−17 vs −30%, P < 0.001). Conclusion: The data from this meta-analysis support current task force criteria for the diagnosis of ARVC. In addition, other RV measures that reflect the complex geometry and function in ARVC clearly differentiated between ARVC and healthy controls and may provide additional diagnostic and management value. We recommend that future working groups consider this data when proposing new/revised criteria for the echocardiographic diagnosis of ARVC.